2018
DOI: 10.1002/hbm.23951
|View full text |Cite
|
Sign up to set email alerts
|

Time‐dependent differences in cortical measures and their associations with behavioral measures following mild traumatic brain injury

Abstract: There is currently a critical need to establish an improved understanding of time-dependent differences in brain structure following mild traumatic brain injury (mTBI). We compared differences in brain structure, specifically cortical thickness (CT), cortical volume (CV), and cortical surface area (CSA) in 54 individuals who sustained a recent mTBI and 33 healthy controls (HCs). Individuals with mTBI were split into three groups, depending on their time since injury. By comparing structural measures between mT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 86 publications
2
5
0
Order By: Relevance
“…Contrary to this, we observed increased CSA in the right lateral occipital gyrus in the acute phase of mTBI. However, CV is a composite of CT and CSA, and changes in CV could be due to changes in CT and/or CSA (Bajaj et al, 2018). Our findings are therefore consistent with previous studies.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Contrary to this, we observed increased CSA in the right lateral occipital gyrus in the acute phase of mTBI. However, CV is a composite of CT and CSA, and changes in CV could be due to changes in CT and/or CSA (Bajaj et al, 2018). Our findings are therefore consistent with previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…Another study reported that mTBI patients at 3-6 months post-injury had lower CSA in right postcentral regions, inferior temporal cortex, and superior frontal areas in comparison with healthy controls (Bajaj et al, 2018). In the same study, the mTBI patients at 6-18 months post-injury showed significantly higher CSA in left postcentral regions, superior temporal areas, and the right isthmus of the cingulate gyrus in comparison with CSA measurements at 3-6 months (Bajaj et al, 2018). These findings imply that alterations in CSA can be used to reflect cortical recovery during the chronic stages of mTBI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early recovery reveals deficits in processing speed (De Monte & Geffen, 2005;Shumskaya, Andriessen, Norris, & Vos, 2012), attention (Catale, Marique, Closset, & Meulemans, 2008;Konrad et al, 2011;Mayer et al, 2012), and episodic memory (Wammes, Good, & Fernandes, 2017), and few have assessed cognitive performance in the chronic mTBI population, who are more than 3 months postinjury. In the chronic mTBI population, behavioral deficits are reported in a majority of participants (McInnes, Friesen, MacKenzie, Westwood, & Boe, 2017), accompanied by neural differences (Eierud et al, 2014;Ham et al, 2014;Pan et al, 2016;Sharp & Ham, 2011;Sharp, Scott, & Leech, 2014;Shenton et al, 2012;Tate, Shenton, & Bigler, 2012) detectible even years after an mTBI (Bajaj, Dailey, Rosso, Rauch, & Killgore, 2018;Dall'Acqua et al, 2017).…”
mentioning
confidence: 99%
“…The purpose of this descriptive study has been to outline the methods used in the CENC Neuroimaging Core and not to tease out the potential clinical significance of the observed cortical thickness findings, or whether or not subsets of volumetric associations relate to certain aspect of mTBI demographics. Nonetheless, the regions of reduced cortical thickness in this CENC investigation have been implicated in other cortical thickness studies of mTBI, PTSD, and symptoms associated with these disorders (Bajaj, Dailey, Rosso, Rauch, & Killgore, ; Govindarajan et al, ; Savjani, Taylor, Acion, Wilde, & Jorge, ). Future CENC studies will more closely examine these relationships as well as the role of other mediators and confounders, including methods for addressing false positive rates in surface‐based anatomical analyses (Greve & Fischl, ).…”
Section: Discussionmentioning
confidence: 54%